Empirical Analysis of The Impact of Public Debt on Macroeconomic - Wafure, Obida Gomna; Musa, Ibrahim; Ahmad, Abdullahi Idris (International Journal of Economics Development Research (IJEDR), 2025)
This study investigates the impact of public debt on Nigeria's macroeconomic indicators, including real gross domestic product (RGDP), unemployment (UNEM), interest rate (INTR), and inflation rate (INFR), from 1980 to 2020. The study utilises the autoregressive distributed lag (ARDL) bounds testing approach for cointegration, and the nonlinear autoregressive distributed lag (NARDL) bounds testing approach. The cointegration analysis reveals a notable symmetric and asymmetric cointegrating relationship, both in the long run, between public expenditure (both external and domestic) and the chosen macroeconomic variables. In addition, the ARDL model demonstrates that Domestic Debt (DD) raises national output but reduces UNEM and INFRs significantly in the long term. However, the results suggest that External Debt (ED) raises UNEM and INTR in the country in the long term. The NARDL model indicates that the positive component of DD raises national output. The study reveals that both domestic and ED have long-term effects on national output, with negative debt reducing UNEM and INTR, and positive ED reducing inflation. Given these results, the federal government should decrease excessive borrowings due to their detrimental impact on macroeconomic indicators in the short and long run. Generate more revenue through tax increment rather than borrowing, diversify the economy into areas like agriculture and mining rather than depending on oil and borrowing, and reduce the leakages (corruption) in the system through effective and efficient use of the anti-graft agencies in Nigeria.